Beyond the horizon adventures in faraway lands - Booz, Patrick R.; Aaronson, Jeffrey; National Geographic Society (U.S.) Book Division (Washington, D.C. The National Geographic Society, 1992)
Travel to some of the world's least known places including Timbuktu in Africa, Muli on the China-Tibet border, and to Iceland.
China: The Kingdom of Muli -- Mali: Lands Along the Niger -- Iceland: Land of Fire and Ice -- Venezuela: Lost World of the Tepuis -- Australia: Song Line of the Kimberley.
Includes bibliographical references (page 196) and index.
Keywords: Voyages and travels